CTLA: Compressed Table Look up Algorithm for Open Flow Switch - Sonai, Veeramani; Bharathi, Indira; Uchimucthu, Muthaiah; S, Sountharrajan; Bavirisetti, Durga Prasad (IEEE open journal of the Computer Society, 2024)
The size of the TCAM memory grows as more entries are added to the flow table of Open Flow switch. The procedure of looking up an IP address involves finding the longest prefix. In order to keep up with the link speed, the IP lookup operation in the forwarding table should also need to be speed up. TCAM's scalability and storage are constrained by its high power consumption and circuit density. The only time- or space-efficient algorithms for improvement are the subject of several research studies. In order to boost performance even further, this study focuses on time and space efficient algorithms. To strike a balance between speedy data access and efficient storage, this study proposes a combination of compression and a quick look-up mechanism to satisfy the space and speed requirements of the Open Flow switch. As the data is compressed, performance improves because less memory is required to store the look-up table and fewer bits are required to search. The look up complexity of proposed approach is O(log\,(log\;n/2)) and average space reduction is 61%.